2005
DOI: 10.1007/s10566-004-2181-9
|View full text |Cite
|
Sign up to set email alerts
|

The Capacity to Change and Child and Youth Care Practice: A Program Example and Framework

Abstract: Child and youth care practitioners are in the practice of facilitating and supporting change in individuals, families and communities. Therefore, as change agents it is important to uncover and understand the perspectives that direct one's practice. Personal and professional experiences, as well as a multitude of theoretical orientations, merge to create a child and youth care practitioner's ''tool box''. This article offers a brief foray into various change theories and provides examples of how these change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Among the contributors of this scenario could be that CYC "finds itself at the bottom of the hierarchy of public and professional perception within the broader field of human services as well as other professionals" (Gharabaghi, 2008, p. 155). Poor public perceptions persist despite evolutions that resulted in CYCWs facilitating and supporting change in individuals, families and communities (Radmilovic, 2005).…”
Section: Practice-related Challengesmentioning
confidence: 99%
“…Among the contributors of this scenario could be that CYC "finds itself at the bottom of the hierarchy of public and professional perception within the broader field of human services as well as other professionals" (Gharabaghi, 2008, p. 155). Poor public perceptions persist despite evolutions that resulted in CYCWs facilitating and supporting change in individuals, families and communities (Radmilovic, 2005).…”
Section: Practice-related Challengesmentioning
confidence: 99%
“…Within the Child and Youth Care literature reviewed the influence of Urie Bronfenbrenner's theoretical perspective on the ecology of human development is evident (Ferguson, Pence, & Denholm, 1993a;Krueger, 2000Krueger, , 2005Maier, 1991;Mattingly et al, 2002;Phelan, 2003;Radmilovic, 2005;VanderVen 2006;White 2007). Clearly, his ideas have resonated within Child and Youth Care and based on the literature reviewed ecological influences, as conceptualized by Bronfenbrenner, can be seen in descriptions of the field, efforts to prepare practitioners for professional practice and in practice.…”
Section: What Is the Influence Of Ecological Theory On Child And Youtmentioning
confidence: 99%
“…For example, Krueger (2000Krueger ( , 2005 points out that youth workers not only directly work with youth in their environments but that their presence in other ecological contexts such as family and community can change these systems. Radmilovic (2005) acknowledges the influence of Bronfenbrenner in her argument that systemic change is necessary in order to support and sustain change in individuals. As VanderVen (2006) states, "…to significantly influence the quality of human services delivered to children requires a comprehensive ecological approach that can influence each of the environmental systems that impinge on children and affect their lives" (p. 254).…”
Section: Ecological Influences -In Practicementioning
confidence: 99%
“…This research intends to contribute answers to the question: do humans have the capacity to change? Radmilovic (2005) reported that when examining change, it is important to discern between different types o f change: development, prevention, and recovery. Change naturally occurs, as a result of human growth and development.…”
Section: Exploring Human Capacity To Changementioning
confidence: 99%